Thomas: The Apostle of Scientists. Issue 2 (3rd April 2017) - Poon, Wilson C. K.
ABSTRACT: Richard Dawkins suggests that the way "doubting Thomas" demanded evidence for Jesus' resurrection should endear him to scientists. A close reading of Chapter 20 of John's Gospel suggests that Thomas' confession of Jesus' divinity does indeed resonate with how scientists make progress, but not because he demanded evidence. Rather, the similarity lies in the way he went beyond the immediate evidence to reach a bold conclusion, the implications of which took a lifetime to work out. A comparison with the way J. J. Thomson discovered the first sub-atomic particle, the electron, shows that this is also how breakthroughs in science happen.